Ultrasonic study of 1-X adamantane (X = F, Cl, Br) compounds at high pressure and at order–disorder transitions. Issue 30 (21st July 2022) - Gromnitskaya, Elena L.; Danilov, Igor V.; Brazhkin, Vadim V.
Abstract : We have detected for the first time the boundaries of the 1-fluoroadamantane HT → MT → LT phase transitions under pressure, and have confirmed that the MT → LT is a second-order phase transition, manifested in anomalies of the elastic properties Abstract : We present an ultrasonic study of the elastic properties of 1-X adamantane (X = F, Cl, Br) during order–disorder and order–quasi-order transitions at various temperatures (77–305 K) and high pressures (up to 1 GPa). On the basis of our ultrasonic experiments, we studied for the first time the high-temperature (HT) Fm 3 m, medium-temperature (MT) P 42 / nmc, and low-temperature (LT) P 421 c phases of 1-fluoroadamantane at high pressures. The elastic properties of these phases at pressures up to 1 GPa at T = 293 and 77 K, as well as at isobaric heating from 77 to 293 K, have been determined. The boundaries of the HT → MT → LT phase transitions have been evaluated, which makes it possible to extend the phase diagram of 1-fluoroadamantane to higher pressures. We have confirmed that the MT → LT transition is a second-order phase transition because it is not accompanied by volume jumps but is manifested in anomalies of the elastic properties and ultrasound transmission both in high-pressure experiments and under isobaric heating. The comparison of the elastic properties of 1-X adamantanes (X = H, F, Cl, Br) has indicated a monotonic dependence at low pressures: the bulk modulus is the highest for adamantane and decreases with an increase of the atomic number of the halogen substitute (from fluorine to bromine).